2008
DOI: 10.1017/s0033291708003449
|View full text |Cite
|
Sign up to set email alerts
|

The association between pre-morbid adjustment, duration of untreated psychosis and outcome in first-episode psychosis

Abstract: Longer DUP is associated with poorer 2-year outcome of psychosis in schizophrenia-spectrum disorders, when pre-morbid functioning and other prognostic factors are controlled for. Impaired pre-morbid development is independently associated with more negative symptoms and poorer social outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
60
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 30 publications
11
60
1
4
Order By: Relevance
“…Longer DUP is associated with a poorer outcome of psychosis at 2 years. 23 A meta-analysis of nine adolescent and adult studies found no association between cannabis use and DUP; however the author noted an association between the timing of cannabis use and DUP. While DUP was shorter in cannabis users in studies where cannabis use was defined in terms of current or recent use; DUP was longer in cannabis users in studies based on lifetime cannabis use.…”
Section: Cannabis and Duration Of Untreated Psychotic Symptomsmentioning
confidence: 99%
“…Longer DUP is associated with a poorer outcome of psychosis at 2 years. 23 A meta-analysis of nine adolescent and adult studies found no association between cannabis use and DUP; however the author noted an association between the timing of cannabis use and DUP. While DUP was shorter in cannabis users in studies where cannabis use was defined in terms of current or recent use; DUP was longer in cannabis users in studies based on lifetime cannabis use.…”
Section: Cannabis and Duration Of Untreated Psychotic Symptomsmentioning
confidence: 99%
“…With respect to schizophrenia, these include the notions that (1) the disorder generally starts in late adolescence/early adulthood, (2) it often remains untreated for months and years before being recognized and adequately treated, and (3) it frequently shows a chronic course, with several relapses or a continuous and progressive deterioration at different levels [13,14]. All these features dramatically impact on the social, family and vocational life of patients and their families.…”
Section: Resultsmentioning
confidence: 99%
“…schizophrenia and bipolar disorder). Many people with FEP do not seek help for themselves [19]: for instance, large sample studies in schizophrenia have found mean DUP values ranging from 8 to 48 weeks in first-episode patients [13,14]. In bipolar disorder, mean DUI values tend to be even longer ranging, from 5 to 10 years [9,20].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with predominantly negative symptoms have poor pre-morbid adjustment during childhood or early adolescence and a low employment rate during adulthood, achieve low educational attainment and exhibit considerable cognitive impairment (Milev et al 2005;Rosenheck et al 2006;Jeppesen et al 2008).…”
Section: Introductionmentioning
confidence: 99%